Expertise and child sex offenders. (January 2015) - Fortune, Clare-Ann; Bourke, Patrice; Ward, Tony
Abstract: Research conducted on criminal expertise contends that offenders obtain specialist knowledge and skills relevant to their domain, and that the successful execution of knowledge and skills is a function of learning and experience. Some child sexual offenders possess domain-relevant competencies such as in the selection and manipulation of victims, decision-making and problem-solving, and eluding detection; these competencies and areas of skill contribute to their sexual offending. In this paper, we first examine Ward's (1999) original application of the concept of expertise to sexual offenders and briefly overview his theory. Second, Bourke, Ward, and Rose's (2012) empirical investigation of Ward's theory with sexual offenders is reviewed and the resulting expertise model is described in detail. Third, theory and research on self-regulation patterns and modus operandi in child sexual offenders are reviewed and its links with expertise are highlighted. Finally, the practice implications of an expertise perspective are discussed.